Communication Patterns of Islamic Religious Instructors In Improving Family Resilience In Bireun District - Nur, T Mursal M; Kholil, Syukur; Faridah, Faridah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to analyze the communication patterns of islamic religious instructors in improving family resilience in bireun district. This research method is qualitative-descriptive. The time required to conduct research on communication patterns of Islamic religious instructors in fostering family resilience is carried out for 6 months, namely from March 2023 to September 2023. Based on the research results, researchers found the communication pattern of Islamic religious instructors with the community or community groups in an effort to increase family resilience is carried out by direct and indirect communication by the instructor to the community. Communication messages carried out by Islamic Religious Counselors with the community or community groups in an effort to increase family resilience are messages related to problems that occur in husband and wife families. Barriers to Islamic religious instructors' communication patterns with the community or community groups in an effort to increase family resilience are psychological barriers, because husband and wife do not want to be honest about all the problems that occur in their household, so that the problems are resolved quickly and do not become drag on. The result of communication between Islamic religious instructors and the community or community groups in an effort to increase family resilience is the awareness of each married couple in communicating with the instructors regarding various problems that occur in their household, so that this makes it easier for the instructors to carry out his duties.